2015
DOI: 10.1007/s11999-015-4290-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With the SIGN Nail in Closed Diaphyseal Femur Fractures Results in Acceptable Radiographic Alignment

Abstract: Background The burden of orthopaedic trauma in the developing world is substantial and disproportionate. SIGN Fracture Care International is a nonprofit organization that has developed and made available to surgeons in resourcelimited settings an intramedullary interlocking nail for use in the treatment of femoral and tibial fractures. Instrumentation also is donated with the nail. A prospectively populated database collects information on all procedures performed using this nail. Given the challenging setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…(2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Complications found by prior studies have included delayed union in 4-34% of patients, and infection in 1-11%, implant failure in 3-4%. (2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Despite their use of heterogeneous outcome measurements, these SIGN nail results have been found to be comparable to those from other studies that evaluated more traditional cannulated interlocking intramedullary nails. (2,12) There are several limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…(2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Complications found by prior studies have included delayed union in 4-34% of patients, and infection in 1-11%, implant failure in 3-4%. (2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Despite their use of heterogeneous outcome measurements, these SIGN nail results have been found to be comparable to those from other studies that evaluated more traditional cannulated interlocking intramedullary nails. (2,12) There are several limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The former was successfully treated with 2-week regimen of 500 mg oral cefuroxime (CEFUREX ® ; Cathay Drug Co. Inc., Makati City, PH) twice daily and the latter, with six weeks of physical therapy. It has been recognized that traditional clinical research using standard follow-up is extraordinarily difficult in the developing world, where resources are limited [ 22 ]. It is financially challenging for our patients to pursue regular follow-up after surgery, and similar to the experiences of Young et al [ 23 ], patients most commonly seek follow-up for the removal of wound sutures or due to development of a complication and less for surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Multiple studies have subsequently shown that the SIGN nail is an effective treatment choice in these circumstances. [ 12 , 14 , 15 , 20 22 ] Carsen et al [ 23 ] recently analyzed the postoperative radiographs of 500 cases in which the standard SIGN nail was used to treat fractures of the femoral shaft. The authors found that 10% of cases demonstrated fracture malalignment greater than 5°.…”
Section: Discussionmentioning
confidence: 99%
“…The SOSD is a robust registry that serves as a model for trauma system data tracking globally. In their large review of the SOSD, Carsen et al [ 23 ] found that >90% of patients treated for femur fractures with the standard SIGN nail had orthogonal imaging adequate for evaluation of post-operative alignment. [ 23 ] Our study found the registry to be similarly adequate but somewhat less comprehensive, with only 80% of the 56 selected cases containing orthogonal views for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation